Design Principles for a Contrail-Minimizing Trial in the North Atlantic - Molloy, Jarlath; Teoh, Roger; Harty, Seán; Koudis, George S.; Schumann, Ulrich; Poll, D. I. A.; Stettler, Marc E. J. (Aerospace, 2022)
The aviation industry has committed to decarbonize its CO2 missions. However, there has been much less industry focus on its non-CO2 emissions, despite recent studies showing that these account for up to two-thirds of aviation’s climate impact. Parts of the industry have begun to explore the feasibility of potential non-CO2 mitigation options, building on the scientific research undertaken in recent years, by establishing demonstrations and operational trials to test parameters of interest. This paper sets out the design principles for a large trial in the North Atlantic. Considerations include the type of stakeholders, location, when to intervene, what flights to target, validation, and other challenges. Four options for safely facilitating a trial are outlined based on existing air-trafficmanagement processes, with three of these readily deployable. Several issues remain to be refined and resolved as part of any future trial, including those regarding meteorological and contrail forecasting, the decision-making process for stakeholders, and safely integrating these flights into conventional airspace. While this paper is not a formal concept of operations, it provides a stepping stone for policymakers, industry leaders, and other stakeholders with an interest in reducing aviation’s total climate impact, to understand how a large-scale warming-contrail-minimizing trial could work.